1999
DOI: 10.1046/j.1523-1747.1999.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

CD11b+ Cells and Ultraviolet-B-Resistant CD1a+ Cells in Skin of Patients with Polymorphous Light Eruption

Abstract: After ultraviolet exposure Langerhans cells (epidermal CD1a+ cells) disappear from the healthy skin, and CD11b+ macrophage-like cells, which are reported to produce interleukin-10, appear in a matter of days. These phenomena are related to the ultraviolet-induced local suppression of contact hypersensitivity reactions. A defect in this suppression might allow inadvertent immune reactions to develop after ultraviolet (over)exposure; i.e., it could cause ultraviolet-B-induced polymorphous light eruption. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 34 publications
5
70
4
Order By: Relevance
“…Although macrophages also express CD11b and infiltrate UVB-irradiated skin, they are improbable candidates for the IL-4 ϩ cells because of the presence of CD36 and the absence of CD15. In connection to this, it was recently shown that the majority of the CD11b ϩ cells, which infiltrate UVB-exposed skin, lack the macrophage marker CD68 (23). Basophils and eosinophils also have a multilobed nucleus and express CD11b and CD15, but they are not known to infiltrate UVB-exposed normal human skin (24), and by means of specific mAbs we demonstrated that these two cell types are absent in irradiated skin.…”
Section: Figure 6 Depletion Of Cd15mentioning
confidence: 55%
“…Although macrophages also express CD11b and infiltrate UVB-irradiated skin, they are improbable candidates for the IL-4 ϩ cells because of the presence of CD36 and the absence of CD15. In connection to this, it was recently shown that the majority of the CD11b ϩ cells, which infiltrate UVB-exposed skin, lack the macrophage marker CD68 (23). Basophils and eosinophils also have a multilobed nucleus and express CD11b and CD15, but they are not known to infiltrate UVB-exposed normal human skin (24), and by means of specific mAbs we demonstrated that these two cell types are absent in irradiated skin.…”
Section: Figure 6 Depletion Of Cd15mentioning
confidence: 55%
“…Therefore, UV exposure induces a systemic and a local increase in 1␣,25-(OH) 2 D 3 in the skin. It is known that after UV exposure, Langerhans cells (epidermal CD1a ϩ cells) disappear from the healthy skin, and CD11b ϩ macrophage-like cells appear in few days (69). Moreover, UV radiation induces apoptosis and suppresses the immune function of epidermal Langerhans cells (70).…”
Section: Effects Of 1␣25-(oh) 2 D 3 On Already Differentiated Immatumentioning
confidence: 99%
“…A key cellular event in UV immunosuppression is the migration of Langerhans cells (LC) from the epidermis to the skin-draining lymph nodes (5) where they mediate the activation of immunoregulatory T cells (6). While LC migration and immune suppression is a normal response to UV in healthy human skin, this may not occur in PLE skin (7)(8)(9). Prophylactic UV photohardening in PLE patients restores the capacity for UVinduced LC migration which is thought to be one of the mechanisms of action of this therapy (10).…”
Section: Introductionmentioning
confidence: 99%